AKTIVITAS MARKETING PUBLIC RELATIONS DALAM MEMBANGUN BRAND POSITIONING DI PT FOODS BEVERAGES INDONESIA - Vrendi Witoko (Universitas Mercu Buana, 2022)
The method used in this study is descriptive qualitative, primary data collection methods with in-depth interview techniques, and documentation, while secondary data collection is done by collecting data through research and library studies and then the validity of the data is tested through triangulation techniques. The results of the research from Marketing Public Relations Activities in Building a Brand Position at PT Foods Beverages Indonesia in the eyes of consumers, through the Drink Promotion at Chatime Setia Budi One Jakarta, which succeeded in making consumers keep buying and even making favorite drinks and maintaining good relations between PT. Foods Beverages Indonesia with its customers, so as to create goodwill and mutual understanding from the public in building customer trust and interest in participating in the Promotion Program organized by PT. Foods Beverages Indonesia. Conclusion of this research Every activity carried out in the company in this case Marketing Public Relations activities have a positive and negative impact in terms of promotions that are held positive impacts that must be able to be maintained in order to make Brand Chatime more advanced and always develop innovations while the negative impacts regarding the program that is carried out because of an existing obstacle must be able to immediately overcome it well in order to achieve a customer or buyer satisfaction to be able to always enjoy the chatime by having fun and comfort.